Nyantri Sebagai Alternatif Mengabdi Sambil Menggali Ilmu Agama di Ribath As-Salma - Moh Fodhil; Ashlihah Ashlihah; Dyah Ayu Sri Hartati; Nur Khaqiqi Issyiami (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Ribath As-Salma is one of the ribaths under the auspices of the Bahrul Ulum Islamic Boarding School Foundation, at times like this there are many Islamic boarding schools that do not bring in their students due to fear and worry about the covid-19 that has spread so far. But not for the As-Salma ribath, this ribath still invites all its students while maintaining and promoting the prescribed health protocols. The purpose of this activity is to improve the understanding and skills of the students of the Bahrul 'Ulum Islamic Boarding School, Ribath As-Salma in reading books and to improve the tutoring for students of the Bahrul'Ulum Islamic Boarding School, Ribath As-Salma Tambakberas Jombang in reading books and forming an activity committee. The methods for implementing community service activities in the KKN-PPM scheme include lectures, discussions, and training methods. Based on the results of community service activities in the KKN-PPM scheme, it can be concluded that these community service activities provide additional knowledge and insight and skills of the students of the Bahrul 'Ulum Islamic Boarding School, Ribath As-Salma Jombang related to reading the yellow book well and establishing a committee. show properly and correctly.